2013
DOI: 10.7455/ijfs/2.1.2013.a7
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants, their properties, uses in food products and their legal implications

Abstract: Oxidation decreases consumer acceptability of food by changing its organoleptic properties, destroying essential nutrients and producing toxic compounds. Antioxidants delay oxidation of lipids in foods as well in human systems. Studies reveal that synthetic antioxidants may trigger diseases in human when consumed over a certain concentration. The toxicological effects of synthetic food antioxidants have been the focus of controversy in recent years. There is scope to use natural antioxidants, present in many c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 136 publications
0
30
0
Order By: Relevance
“…() and Thorat et al. () showed that BHT and BHA are quite volatile and easily decompose at high temperatures. The observed efficiency of the extract in prolonging induction time of palm olein as well as its good protection factors might be attributed to the phenolic antioxidants present in this extract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…() and Thorat et al. () showed that BHT and BHA are quite volatile and easily decompose at high temperatures. The observed efficiency of the extract in prolonging induction time of palm olein as well as its good protection factors might be attributed to the phenolic antioxidants present in this extract.…”
Section: Resultsmentioning
confidence: 99%
“…() and Thorat et al. (), BHA and BHT are quite volatile and easily decomposed at high temperatures. Today, the increasing consumer awareness of synthetic food additives and safety has prompted increase interest in the use of natural antioxidants as alternatives to synthetic antioxidants, because of their potential health benefits (Krishnaiah et al.…”
Section: Introductionmentioning
confidence: 96%
“…In order to have a standard antioxidant activity measurement system to compare with natural antioxidants and to be incorporated into food, synthetic antioxidants have been developed. Synthetic antioxidants compounds are widely used in food products to inhibit progress of lipid oxidation [31]. In the United States, the following synthetic antioxidants have been evaluated by the FDA and are the most widely used: tert-butylhydroquinone (TBHQ), butylated hydroxyanisole (BHA), butylated hydroxytoluene (BHT) and propyl gallate [32].…”
Section: Resultsmentioning
confidence: 99%
“…The global trend to avoid or reduce the use of synthetic additives, such as butylated hydroxytoluene (BHT) and butylated hydroxyanisole (BHA), has resulted in a need to identify natural alternative sources of food antioxidants [10]. Therefore, there is a growing interest in the use of natural antioxidants in the food industry, not only for application as preservatives but also for the potential benefits to human health.…”
Section: Introductionmentioning
confidence: 99%